Prediction of 10 Years and Lifetime Atherosclerotic Cardiovascular Disease (ASCVD) Risk Among Working Physician of CMCH - Awal, Anisul; Tareq, Nuruddin; Bhattacharjee, Biplob; Chowdhury, Ibrahim; Dey, Ashish; Das, Probir Kumar; Roy, Noresh Chendra; Shahin, Abul Hossain; Jahangir, Nuruddin; Das, Sandipan; Siddique, Salehuddin; Ahmed, Shakera; et al. (University Heart Journal, 2018)
Background:Cardiovascular diseases (CVD) still represent the leading cause of morbidity and mortality, worldwide. As, physicians have a vital role in battling the CVD epidemic by counseling and motivating people to reduce their risk, they should also set an example by taking care of their own health. Objective: To estimate the CVD risk factors prevalence and predict 10 years & lifetime atherosclerotic CVD (ASCVD) risk among physician. Method: Data was collected for this cross-sectional study from 137 working physicians of Chittagong Medical College Hospital on 17th January, 2017. The participants filled a structured questionnaire followed by physical and biochemical measurements including BMI, blood pressure, waist circumference, lipid profile, and fasting blood glucose. We estimated the 10-year predicted risk for ASCVD events (myocardial infarction, coronary insufficiency, atherothrombotic stroke, or CVD death) for the physicians >40 years of age and lifetime predicted risk for ASCVD was estimated for all physicians irrespective of age. Result: Most of the physician irrespective of sex had high lifetime predicted risk of ASCVD (68.4% female, 77.8% male & 75.2% total, P>0.05). Regarding 10-year predicted risk of ASCVD among the physician >40 years of age 24.0% female and 40.6% male physician had moderate to high risk. The following overall prevalence rates of risk factors were reported: current smoker 6.7%, obesity 86.1%, reported hypertension 21.1% and DM was 11.9%.The prevalence of total cholesterol levels e”200 gm/dl was 49.6% and LDL levels >130 mg/dl 46.7% , HDL levels (d”40 mg/dl) was 64.2% and high fasting blood glucose ( >126 mg/dl) was 27.7%. The majority of the participants (61.31%) had > 3 risk factors. Only 14.59% had either no or less than 3 CVD risk factors. Conclusions: Prevalence CVD risk factors were high among working physicians and most of them had high lifetime or 10 years predicted risk for ASCVD events. University Heart Journal Vol. 12, No. 2, July 2016; 68-75